Letter from D. R. King to James Curtis Booth - King, D. Rodney (1862)
D. Rodney King writes to inform James Curtis Booth (1810-1888) that King has returned the manuscript lent to him by Booth.
Keywords: Booth, James Curtis, 1810-1888